048 Cannabis-based medicinal products for neurological disorders: a study of 75 patients. Issue 6 (27th May 2022) - Weatherall, Mark
Abstract : Cannabis-based medicinal products (CBMPs) were approved for use by specialist medical practitioners in the UK in 2018. Licensed indications for CBMPs are limited, but studies have suggested potential benefits from the use of CBMPs across a number of neurological conditions. I present details of 75 neurology patients presenting to a UK-based CQC-registered medical cannabis clinic between December 2019 and January 2021. The most common reason for presentation was epilepsy (22 patients), followed by migraine (19), and MS (12). Small numbers of patients were seen with other neurological disorders. 23 patients had never used cannabis or cannabis-based products; 29 had taken OTC products, 17 had used cannabis recreationally, and 6 patients had previous taken prescribed CBMPs. 15 patients were not prescribed CBMPs. Of these 5 were deemed unsuitable because other licensed treatment options had not been sufficiently explored. CBMPs were generally well tolerated, only 4 patients experiencing adverse effects from THC (somnolence, nausea). Of 60 patients treated, follow-up is available for 46. Of these, 23 (50%) found CBMPs helpful in treating their neurological symptoms, and 11 (24%) found CBMPs helpful in improving their general quality of life. 12 (26%) patients did not find CBMPs helpful. In a real world setting, therefore, patients can find CBMPs helpful for improving neurological conditions, and quality of life. Further studies would be helpful to determine optimal dose and timing schedules for future clinical trials. mark: weatherall1@nhs.net 49